BERYLLIUM DRIVEN HEMATOLOGICAL AND SEROLOGICAL ALTERATION; THAT CURED BY CHELATION VIA NARINGENIN IN ALBINO RATS - ANJANI VERMA; SAMRAT RAKSHIT; SATYENDRA KUMAR NIRALA; MONIKA BHADAURIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Environment faces range of pollutions threats due to extensive industrialization and deforestation. In exists scenario metal contamination deadly one among them. Beryllium is 44th most abundant element in earth crust which executes their discharge in society through fossils fuel combustion besides daily routines things as in chips of electric gadgets jewelry, dental crown. The objective of the present investigation was the reduction of beryllium harmful effect through naringenin in female albino rats. Methods: Female rats were administered by 1mg/kg dose intraperitoneally daily for 28 days alone as well as before/along with three doses (12.5, 25, and 50 mg/kg) of naringenin orally (7 days once in day). Hematological and serological analysis was performed for this clinical research. Results: Beryllium exposure caused severe alteration in hematological markers evident by a significant diminishment of hemoglobin, red blood corpuscles, mean corpuscular hemoglobin concentration and hematocrit and promoted the level of white blood corpuscles and platelets. Similarly, serological parameters; triglycerides cholesterol and glucose were altered significantly as the response of lipid bilayer peroxidation. All these variables were retrieval near to control ardently by three doses of naringenin. Conclusion: In short naringenin might be useful as in natural chelation for beryllium body burden.